Slip‐Tremor Interaction at the Very Beginning of Episodic Tremor and Slip in Cascadia - Yuji Itoh; Anne Socquet; Mathilde Radiguet (AGU Advances)
Abstract In Cascadia, the concomitance of slow slip events (SSE) and tremors during Episodic Tremor and Slip (ETS) episodes is well documented. Brittle tremor patches embedded in the ductile matrix deforming aseismically is the most common concept for the fault structure, but whether tremors and their patches impact the SSE initiation is under debate. This study focuses on 13 initiations of major Cascadia ETS. Limited observational constraints exist on the details of ETS initiation because spatiotemporal SSE inversions usually over‐smooth their temporal evolution. Scrutinizing tremors and SSE at the beginning of major ETS events gives us insights into their mechanical relationship. We directly retrieve the temporal evolution of the SSE moment by stacking sub‐daily Global Positioning System (GPS) time series at multiple sites, without slip inversions. Comparison of the GPS stack with tremor count demonstrates that SSE moment release accelerates drastically ∼1 day after the onset of vigorous tremor activity. On the other hand, once the SSE moment release accelerates, the tremor area expands more rapidly, suggesting that the growth of the ETS occurs through a feedback mechanism between slip and tremor once the SSE is well developed. By combining these and previous observations, we propose a conceptual model of ETS initiation: heterogeneous interface strength limits the growth of SSE with unruptured tremor patches acting as relatively high‐strength pins contributing to this heterogeneity. In other words, major ETS emerges probably only when collective tremor patches are critically stressed.